Oxidative Intramolecular 1, 2‐Amino‐Oxygenation of Alkynes under AuI/AuIII Catalysis: Discovery of a Pyridinium‐Oxazole Dyad as an Ionic Fluorophore. (21st December 2016) - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Rajamohanan, Pattuparambil R.; Kulkarni, Prasad P.; Patil, Nitin T.
Abstract: Oxidative intramolecular 1, 2‐amino‐oxygenation reactions, combining gold(I)/gold(III) catalysis, is reported. The reaction provides efficient access to a structurally unique ionic pyridinium‐oxazole dyad with tunable emission wavelengths. The application of these fluorophores as potential biomarkers has been investigated. Abstract : Farbwahl : Die Titelreaktion bietet Zugang ionischen Pyridinium‐Oxazol‐Dyaden mit außergewöhnlichen Strukturen und einstellbarer Emissionswellenlänge. Die Fluorophore wurden auf ihre Tauglichkeit als Biomarker hin untersucht.